Renewable glycerol esterification over sulfonic-modified mesoporous silicas - Popova Margarita; Lazarova Hristina; Szegedi Agnes; Mihályi Magdolna R.; Rangus Мojca; Likozar Blaz; Dasireddy Venkata D.B.C. (Journal of the Serbian Chemical Society, 2018)
SO3H-functionalised mesoporous materials with different pore structures (SBA-15 and SBA-16) were prepared by the post-synthesis surface modification. The materials were thoroughly characterized by X-ray powder diffraction, nitrogen physisorption, temperature-gravimetric analysis, elemental analysis and solid state NMR spectroscopy. The acidic properties were investigated by the temperature-programed desorption of ammonia. The catalytic performance of SO3H-functionalised mesoporous materials was studied in glycerol esterification with acetic acid.The different amount of silanol groups in the initial SBA-15 and SBA-16 silicas predetermined the different amount of propylsulfonic groups which are formed in them and therefore significantly influenced the acidity and the catalytic performance in glycerol esterification. Much higher amount of Brönsted acid sites was generated in SO3H modified SBA-15 catalyst, which exhibited higher activity to value-added triacetyl glycerol.